Política social Brasileira: Conquistas e desafios - Milko Matijascic (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Since redemocratization in 1985, Brazil's system of social protection became more focused on the neediest while at the same time emphasizing universal access. In a context of severe inequality, the sub-national units of government played a greater role in reaching the broader population. Yet Brazil's social protection model favors cash transfers over social services, and reduces inequalities in the context of a highly unequal labor market. Strategies based on cash transfers appear to have reached their limits, because they are not the most effective way to promote equality and generate opportunities, when compared to the outcomes obtained by social service provision. Furthermore, while much progress toward reducing inequality has been achieved, benefits and services continue to fall short of what might be considered a "welfare state" or Dynamic Social Security.
Keywords: I30; 330; social development; social policy; public policy evaluation